Replacement of rice with little millet in kheer - Mor, Chetna; Dharaiya, Chetan N; Pinto, Suneeta V; Prajapati, Jashubhai P (Indian Journal of Dairy Science, 2017)
The present investigation involved preparation of kheer by replacing rice with  little millet @ 3.0 %( R1), 4.0 %( R2), and 5.0 % (R3) w/w of milk and concentrating it to different ratios viz. 1.6(C1), 1.8(C2), and 2.0(C3). Increase in rate of addition of little millet resulted in significant (P < 0.05) decrease in TS, fat, sucrose, lactose and protein whereas ash content was increase significantly (P < 0.05). With increase in ratio of concentration TS, fat, sucrose, lactose, protein, and ash content were increased significantly (P < 0.05). Both the parameters had significant (P < 0.05) effect on overall acceptability scores of kheer. The highest mean scores for colour and appearance,  consistency, flavour, sweetness and overall acceptability respectively were obtained with interaction effect of R2 × C3 (4 % little millet and 2.0 times ratio of concentration) having yield of kheer 66.5 % on milk basis. During storage in polystyrene cups at refrigerated temperature (6±1°C) the pH decreased significantly (P < 0.05) while acidity and viscosity increased. The SPC increased from 1.65 CFU/g to 5.1 CFU/g at the end of 10 days storage. The little millet kheer was acceptable up to 10 days of storage at refrigerated temperature (6±1°C).